2002
DOI: 10.1038/sj.cgt.7700450
|View full text |Cite
|
Sign up to set email alerts
|

Early gene therapy–induced apoptotic response in BT4C gliomas by magnetic resonance relaxation contrast T1 in the rotating frame

Abstract: The design and evaluation of therapeutic gene transfection protocols and vectors are under extensive development. Magnetic resonance imaging ( MRI ) techniques can aid considerably in the development of experimental treatment approaches, as well as in determining treatment response by observing gross tissue morphology. However, through a unique set of contrast parameters, namely T 1 , T 2 , and diffusion, more information about tissue status can be obtained while delineating and classifying tumor characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 36 publications
4
56
1
2
Order By: Relevance
“…The cell density was 183 Ϯ 13, 154 Ϯ 14, 109 Ϯ 4, and 71 Ϯ 2 ϫ 10 3 cell/mm 3 in days 2, 4, 6, and 8 of treated tumors, respectively; day 6 and 8 values were significantly less than that at day 0 (p Ͻ 0.01). These observations confirmed that gene therapy had induced PCD (14,22), resulting in severe cell loss in the gliomas.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The cell density was 183 Ϯ 13, 154 Ϯ 14, 109 Ϯ 4, and 71 Ϯ 2 ϫ 10 3 cell/mm 3 in days 2, 4, 6, and 8 of treated tumors, respectively; day 6 and 8 values were significantly less than that at day 0 (p Ͻ 0.01). These observations confirmed that gene therapy had induced PCD (14,22), resulting in severe cell loss in the gliomas.…”
Section: Resultssupporting
confidence: 77%
“…In some animals, 1 H NMR spectra were also acquired from the same voxel using the localization by adiabatic selective refocusing (LASER) method as described previously (21) (TR, 8.8 s; TE, 32 ms; SW, 2.5 kHz; 13,000 data points). Metabolite concentrations were quantified from STEAM spectra using non-suppressed water peak as a reference (0.787 kg/kg of fresh untreated BT4C tumor tissue) (22), corrected for T 1 saturation effects because of water accumulation during PCD, using the T 1 values recently reported (22).…”
Section: Methodsmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy is emerging as a highly useful tool for this purpose (Hakumaki et al, 2002;Kauppinen, 2002). In the present work, we evaluated the relevance of MLs and Chocontaining compounds detected in vivo by 1 H MRS in a xenograft model of human neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical applications of ULFMRI of brain might also include monitoring the progression of Alzheimer's and Parkinson diseases, based on changes in T 1ρ contrast previously demonstrated at high field (56-58). Finally, high-field T 1ρ contrast imaging has also been suggested as a potential biomarker for gene therapy of tumors (59,60). Although ULFMRI still requires significant development to achieve clinically useful spatial resolution with an acceptable imaging time, it may ultimately find novel clinical applications that complement those already established with HFMRI.…”
Section: Discussion and Outlookmentioning
confidence: 99%